ANALYSIS OF ATTITUDE AND INTEREST AS INDICATORS OF THE EFFECTIVENESS OF IMPLEMENTING ELECTRONIC SIGNATURES ON ELECTRONIC MEDICAL RECORD DOCUMENTS IN IMPROVING THE QUALITY OF SERVICE (Survey Study at Marthen Indey Hospital Jayapura) - Astrodita Adya Seta; Sri Rochani Mulyani; Widjajanti Utoyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Along with the rapid development of information and communication technology, the health sector continues to transform in terms of management and information. Management of patient data is very important to support diagnostic decision making. Electronic Medical Records (eMR) emerged as a computerized solution for storing demographics, medical data and supporting decisions in making diagnoses. RME administration at Health Service Facilities can be equipped with an Electronic Signature (eSig). This signature is used as a verification and authentication tool in recording and documenting clinical information. Implementing the RME application with eSig in hospitals can help improve the quality of health services and the efficiency of medical data processing. The aim of this research is to find out and analyze in more depth the policies, socialization, effectiveness, attitudes and interests in using eSig in eMR which can improve the quality of patient care. This research is a qualitative descriptive research using direct observation, interviews, documentation and literature. Informants in the research were the Head of the Hospital, doctors, nurses, medical records officers, patients, and experts. The results of research using NVivo14 software via Matric Coding and Nodes by Project Map, show that attitudes and interests are influenced by age and socialization with officers. Ages 20-24 years have high attitudes and interest in using eSig in eMR, while ages over 40 years have low attitudes and interest. Socialization is carried out to improve skills that can improve officers' attitudes and interests in using eSig in eMR. High attitudes and interest support the success of implementing eSig on eMR which will improve the quality of service at Marthen Indey Hospital Jayapura.